Magneto-Induced Normal Stress of Magnetorheological Gel Under Quasi-Statically Monotonic and Periodically Cyclic Loading - Mao, Runsong; Ye, Xudan; Wang, Huixing; Zhang, Guang; Wang, Jiong (Frontiers in Materials, 2021)
Magnetorheological (MR) gel, an analogue of MR fluid, is a novel kind of magnetic-responsive material. In this paper, the influence of quasi-statically monotonic loading and periodically cyclic loading on the normal stress behavior of MRG is systemically investigated. Firstly, carbonyl iron powder (CIP) and soft polymer were adopted for the fabrication of MRG. Then, the variations of normal stress with shear strain were tested under different excited magnetic fields, shear rates, CIP contents and shear strain amplitudes. It was found that the normal stress behavior of MRG exhibits three prominent stages: a sudden rise at the beginning, followed by a rapid decrease and a final steady-state value. The experiments also indicated that the excited magnetic field, compared with other influencing factors, has the most critical effect on the normal stress behavior of MRG. The corresponding mechanisms of various phenomena were methodically discussed. Furthermore, the ratio of shear stress to normal stress was proposed for better comprehending the mechanism of the evolution of internal microstructures of MRG and MR effect from a novel perspective. The results implied that the ratio has a close relation to the excited magnetic field and CIPs content of MRG. The increase of normal stress is helpful for the fabrication of MRG with high-efficiency MR effect.